Alternative sweeteners - Nabors, Lyn O'Brien, 1943- (CRC Press, 2012)
"The fourth edition of Alternative Sweeteners follows the same formula as the previous three books by discussing each sweetener in terms its characteristics. Qualities covered include means of production, physical characteristics, utility, and relative sweetness (compared to sucrose). Technical qualities covered include admixture potential, application, availability, shelf life, transport, metabolism, carcinogenicity, and other toxicity evaluation data. A new chapter on the sweetener Advantame has been added, and new contributors have updated information throughout the book. Also new is a section on how Stevia sweeteners have been examined and deemed safe by the Joint FAO/WHO Expert Committee on Food Additives and the US FDA"--Provided by publisher.
Keywords: Sweeteners.; elektronické knihy; electronic books